Osteoblastoma of the Lateral Skull Base: Work-Up, Surgical Management, and a Review of the Literature” - Craig Miller; Rihan Khan; G. Michael Lemole Jr.; Abraham Jacob (Journal of Neurological Surgery Reports, 2013)
Abstract